Microfinance and poverty in Indonesia: the macro impact of people’s credit bank - Ismail, Munawar; Santoso, Dwi Budi; Satria, Dias (Journal of Business Economics and Management, 2024)
The purpose of this paper is to investigate the role of people’s credit banks (BPRs), a predominant form of microfinance in Indonesia, in mitigating poverty. Using panel data from 31 provinces in Indonesia, this study employs static panel and panel models with instrument variables. Our findings substantiate that BPR credit significantly contributes to poverty reduction across various indices, including headcount poverty, poverty gap, and poverty severity measures. The empirical results offer valuable insights into the efficacy of targeted microfinance as a potent tool for poverty alleviation in developing economies.